Baramasa - Riaz, Ghulam Fariduddin (Oxford University Press, 2002)
From the award-winning poet, G. F. Riaz, this new anthology of poems is organized around the Baramasa--the Punjabi calendar year--and thematizes aspects of life in rural Pakistan